Interpreting the Main Power Characteristics Choice of the Wheel Vehicles Guided Cushioning System - Bogdan Sokil; Oleg Lyashuk; Mariya Sokil; Yuriy Vovk; Volodymyr Dzyura; Victor Aulin; Roman Khoroshun (Communications - Scientific letters of the University of Zilina, 2021)
The method of investigation of the non-linear vibrations of the wheel vehicles with the guided cushioning system has been developed. It is based on the idea of the perturbation methods combined with the theory of special periodic Atebfunctions. All these made possible to obtain analytical relations, which describe the characteristic features of the cushioning area vibrations. These relations can be the basis for creation of the software product of the guided cushioning system with the purpose to minimize the dynamic loadings on the transported people and cargo and to increase the stability characteristics of the vehicle movement along the curvilinear areas of the bump road.